Strategi Guru Madrasah Ibtidaiyah Dalam Menanamkan Nilai-Nilai Keislaman Pada Siswa di Era Digital - Suryani, Irma; Sholeh, Asmar (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2024)
This study aims to explore the strategies implemented by Madrasah Ibtidaiyah teachers at SD Al-Ittihadiyah Laut Dendang in instilling Islamic values in students in the digital era, as well as the challenges faced in the process. This study uses a phenomenological approach with qualitative methods, involving observation, interviews, and document analysis as data collection techniques. The results of the study indicate that teachers employ strategies such as the use of digital media, a contextual approach based on daily life, and modeling through concrete actions to instill Islamic values. However, the main challenges faced include the negative influence of digital content that is inconsistent with Islamic teachings and resource limitations, both in terms of time and facilities. The implications of this study indicate the importance of developing teaching strategies that utilize technology wisely, as well as the need for policies that support digital facilities in schools. This is expected to strengthen the internalization of Islamic values in students amid the rapid development of digital technology.